1998
DOI: 10.1159/000045024
|View full text |Cite
|
Sign up to set email alerts
|

Acute Volume Expansion and Salt-Loading Studies in Rats

Abstract: Differences have been postulated for the mechanism of natriuresis due to atrial natriuretic peptide (ANP), salt loading with high salt diet (HS) and acute volume expansion (AcVE), in particular between AcVE and ANP based on the observed synergism between the two. Therefore the effects of and the interaction between the three were investigated in rats. ANP and AcVE produced the same natriuresis in HS as in normal salt (NS) rats and, in both, the actions of ANP and AcVe were significantly additive showing simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…It is also possible that the acute natriuretic response to ANP has been amplified by volume expansion, probably through an increase in distal delivery of fluid. Therefore, the results of this study would agree with published findings that demonstrated that during large volume expansion (15% body weight) factors other than those acting in the proximal tubule could play a significant role in more distal nephron segments to produce final natriuresis (32) such as the renal nerves, aldosterone, renninangiotensin system, vasopressin , prostaglandins and physical factors (9,20,28,34).…”
Section: Discussionsupporting
confidence: 92%
“…It is also possible that the acute natriuretic response to ANP has been amplified by volume expansion, probably through an increase in distal delivery of fluid. Therefore, the results of this study would agree with published findings that demonstrated that during large volume expansion (15% body weight) factors other than those acting in the proximal tubule could play a significant role in more distal nephron segments to produce final natriuresis (32) such as the renal nerves, aldosterone, renninangiotensin system, vasopressin , prostaglandins and physical factors (9,20,28,34).…”
Section: Discussionsupporting
confidence: 92%
“…Even if there is a clear relationship between blood pressure and extracellular salt and volume, blood pressure changes during acute volume expansion remain quite controversial 4,21 . There is evidence indicating that saline loading produces an increase in arterial pressure in awake and anaesthetized dogs, whereas other studies have shown that arterial pressure is not altered in anaesthetized rats 1,3,22 . The diverse haemodynamic responses to extracellular volume expansion are probably caused by the different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A protein load (115) or feeding (420) increases urinary dopamine that may be secondary to an increase in l -DOPA synthesis. Most studies have shown that a low sodium diet is associated with low urinary dopamine, while a high sodium diet is associated with increased urinary dopamine (9, 11, 40, 42, 43, 86, 214, 253, 352, 420, 443, 504, 577, 654). This may be related to increased spillover of l -DOPA into the arterial blood (214,229), although plasma l -DOPA levels are not increased with high sodium diet.…”
Section: Structure and Function Of The Renal Dopaminergic Systemmentioning
confidence: 99%
“…There is a clear interaction between dopamine receptors and ANP. The natriuretic response to ANP requires an intact renal dopamine system (263, 392, 481, 504, 574, 659). The natriuretic effect of ANP is abolished by D 1 R but not D 2 R antagonists (246, 316, 375, 393, 463) or carbidopa, an inhibitor of dopamine synthesis (309).…”
Section: Dopamine Receptor Interactionsmentioning
confidence: 99%